Web-Based Neighbourhood Head Performance Information System In Medan Labuhan Sub-District - Arrafii Sihotang, Bambang; Rahmadani; Hendry (Cattleya Darmaya Fortuna, 2025)
Performance appraisal of neighborhood heads at the urban village level is often done manually and subjectively, resulting in inaccuracies and unfairness in the evaluation process. This research aims to design and develop a web-based Neighborhood Head Performance Assessment Information System in Medan Labuhan Subdistrict that integrates the Analytical Hierarchy Process (AHP) method. This system was built using the Waterfall method approach and developed with Flutter and Pocketbase technology. Data collection was conducted through in-depth interviews, questionnaires, observations, and documentation studies, which were then analyzed qualitatively and quantitatively using thematic analysis techniques and the System Usability Scale (SUS). The test results show that the system is able to manage criteria data, weighting, candidates, and assessment reports in real-time and efficiently. The system not only improves the objectivity of the assessment, but also supports transparency and community participation in the local governance process. Some suggestions for further development include optimizing backend performance, adding offline mode, and notification features.